Simulation design and analysis 9-level H-bridge single phase stepdown cyclo inverter - Setiyono, Setiyono; Wibowo, Kunto (Institute of Advanced Engineering and Science, 2023)
This DC-to-AC voltage converter is designed for output frequency controlled by a 9-level cascade H-bridge cyclo inverter with pulse width adjustment. The aim of the study was to determine the pattern and format of the voltage, output frequency, and Total Harmonic Distortion index of a 9-level IGBT cyclo inverter. The method used is to build a unidirectional power converter design modeling into 9 alternating levels with cyclo converter-controlled frequency settings using the Simulink MATLAB tool. The cyclo converter section is constructed with two P and N converters in a parallel arrangement. The frequency and trigger pulse width of both converters control the output voltage and frequency format of the cyclo inverter. The test results show a series of ladder waves with an output frequency, of (1/2f, 1/3f, 1/4f, 1/5f, 1/6f, 1/7f, 1/8f, 1/9f, and 1/10f). The simulation results show that the nth input frequency divider waveform is characterized by the emergence of a number of step pulses of n positive half cycles and negative half cycles. The Total Harmonic Distortion Index gets bigger when the system circuit is designed at a low frequency. This modeling can be implemented into a prototype that is used for variable-speed DC motor drivers.